Biomineralized Mesocrystal KCl Microreactor for Solid‐State Synthesis of Non‐Oxide Nanomaterials. Issue 2 (6th January 2022) - Du, Yongxu; Liu, Wei; Fan, Hongguang; Dong, Tiantian; Jin, Yongcheng; Liu, Shuang; Li, Mingzhu; Hu, Maofeng; Duan, Zhipeng
Abstract: Inspired by natural biomineralization, a biomineralized microreactor with a mesocrystal KCl shell (BM‐KCl‐MMs) is made by a facile freezing dry process, exhibiting a good availability for high‐temperature solid‐state synthesis of nanomaterials. Benefiting from the good thermal stability, stiffness, and mechanical strength of KCl mesocrystal shells, the employment of BM‐KCl‐MMs in the transition metal (TM)–S–Se system not only realizes for the first time, the production of TMS x Se2− x /C nanocomposites in air atmosphere, but also reaches a high reagent‐utilization and high yield, as well as minimum wastes. More importantly, based on the soaking effect of the KCl shells, the resultant stable reaction microenvironment inside endows the microreactors with a well‐controlled synthesis of nanomaterials with very even size, uniform dispersion, and novel functionalities. As one example, the as‐prepared MoS x Se2− x /C composites as the electrodes of K‐ion batteries and K‐ion hybrid supercapacitors deliver the state of the art cycling capability of 248 mAh g −1 at 2 A g −1 after 5000 cycles and an 87.1% capacity retention at 5.0 A g −1 after 20 000 cycles, respectively, demonstrating a significant potential of BM‐KCl‐MMs on design and synthesis of novel functional nanomaterials. Abstract : A biomineralized mesocrystal KCl microreactor ensures that the high‐temperature solid‐state synthesis of nanomaterials achieve a better control of the process.